The Impact of Exchange Traded Funds and Index Futures of Five Asian Equity Markets - Empirical Evidence - Yong, Sern Cherk (2014)
Previous empirical studies focus more on the underlying index of the futures contract as the spot market is in the process of discovering which of the spot and the futures market lead the price formation. For this research, two derivative products from five Asian countries are utilised in order to show whether the Exchange Traded Funds (ETFs) or the futures index lead in price discovery. The ETFs are a perfect substitute for stock indexes because it tracks the performances of stock indexes as its benchmark. Using intraday 5-minute average price transaction data, a linear vector error correction model is applied to estimate the coefficients for the purpose of determining the contribution of both markets to the process of price discovery. This process uses the common factor weights as advocated by Schwarz and Szakmary (1994). The overall results suggest that futures still dominate in the lead-lag price relationship. Moreover, volatility is identified as the driving force behind the process of price leadership of the futures market. Nonetheless, futures market does not necessarily lead in price formation since there is a significant improvement in information distribution in the ETF markets during volatile periods.